Implementasi Aliran Progresivisme dalam Pembelajaran Menurut Filsafat Pendidikan dan Perkembangan Kurikulum di Indonesia - An Nisa Rahma; Hafidhotur Rohmah; M. Yunus Abu Bakar (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2022)
The Implementation of Progressivism in learning according to the philosophy of Education and curriculum development in Indonesia aims to make readers understand the implementation of Progressivism and examples of its curriculum which are explained in detail in the Education curriculum in Indonesia. The method used in this article is a qualitative method using a library research approach. In this stage, the researcher tries to select data (books) that are related to the flow of progressivism and its characters. The results of this study indicate that the flow of progressivism is a school of educational philosophy that supports the changes and progress of education in accordance with the changing times. This flow was influenced by William James, John Dewey, and Hans Vaihinger. The goal of the flow of progressivism is to produce students who can think practically, and can solve problems effectively in an increasingly developing and advanced environment by using their experiences. Educators only act as motivators, give directions or mentors of students. Progressivism flow uses non-authoritarian learning and indoctrination. The curriculum used is flexible, free, open and does not indoctrinate students. Indonesia is one of the countries that is developing its curriculum so that it is not left behind and can compete with international education.